Bordeaux 2018: Wine, Cheese, and γδ T Cells - Edelblum, Karen; Gustafsson, Kenth; Pennington, Daniel J.; Willcox, Benjamin E.; Ribot, Julie C. (Frontiers in Immunology, 2019)
The first ‘International γδ T cell conference’ took place in Denver, CO (USA) in 2004. Since then, a new meeting is held every two years. During each conference, all participants voted to choose between candidate bids for where to hold the next conference. At the conference held in London in 2016, a majority opted for the bid from a team proposing the 2018 event be held in Bordeaux, France – which is where we therefore gathered on 7-10th of June 2018. The meeting was an undisputed success and it gave us the opportunity to take stock of the increasing basic knowledge about γδ T cells as well as the rapidly expanding interest and activities developing using γδ T cells towards clinical applications. If we were to point to one single ‘take home lesson’; we could say that this conference underlined the impression that the γδ T cell compartment comprises functionally diverse subsets that can occupy niches contributing to either innate or adaptive immunity, and potentially the interface between the two.